Effects of intensive rosuvastatin on ventricular remodeling and cardiac function in elderly patients with STEMI undergoing PCI - Qin, Yiran; Jin, Siyi; Sun, Xusen; Luo, Rong; Liu, Haibo (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAcute myocardial infarction in the elderly often leads to significant left ventricular structural remodeling, which adversely affects prognosis. This study aims to evaluate the effects of intensive rosuvastatin therapy on markers of ventricular remodeling and cardiac function following percutaneous coronary intervention (PCI) in elderly patients with ST-segment elevation myocardial infarction (STEMI).MethodsThis study enrolled 100 patients aged ≥60 years with STEMI who underwent emergency PCI. The patients were randomly assigned to either an intensive therapy group (n = 50), receiving rosuvastatin 20 mg/day, or a control group (n = 50), receiving 10 mg/day. Differences in lipid profiles, serum inflammatory markers, fibrosis indicators, and echocardiographic parameters were compared between the two groups before treatment and after 8 weeks of therapy.ResultsAfter 8 weeks of treatment, the intensive group showed significantly reduced serum inflammatory levels compared to the control group, including C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and intercellular adhesion molecule-1 (ICAM-1) (P < 0.05). Markers of ventricular remodeling also improved in the intensive group, with lower levels of N-terminal pro-B-type natriuretic peptide (NT-proBNP), galectin-3, and matrix metalloproteinase-9 (MMP-9) compared to the control group (P < 0.05), while levels of tissue inhibitor of metalloproteinases-4 (TIMP-4) were significantly higher (P < 0.05). Additionally, after treatment, the intensive group demonstrated significantly higher levels of left ventricular ejection fraction (LVEF), stroke volume, and peak systolic velocity at the lateral mitral annulus (TDI s′-l) compared to the control group (P < 0.05). Conversely, the left ventricular end-systolic diameter (LVESD) and left ventricular end-systolic volume (LVESV) were significantly lower in the intensive group than in the control group (P < 0.05).ConclusionIn elderly patients with STEMI, high-dose rosuvastatin demonstrates superior therapeutic efficacy compared to conventional-dose therapy in alleviating inflammatory responses, improving ventricular remodeling, and enhancing cardiac function.Clinical Trial Registration[www.chictr.org.cn], identifier [ChiCTR2200066956].